2016
DOI: 10.1002/ijc.30047
|View full text |Cite
|
Sign up to set email alerts
|

NSCLC harboring EGFR exon‐20 insertions after the regulatory C‐helix of kinase domain responds poorly to known EGFR inhibitors

Abstract: Anecdote clinical observations hint that non-small cell lung cancer (NSCLC) with exon-20 insertions might respond poorly to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), contrasting to those with classic mutations. Lack of patient-derived experimental models has been a major hurdle for the discovery of new treatment for the diseases. We established two NSCLC-PDXs harboring two different exon-20 insertions, LU0387-adenocarcinoma (ADC) with a nine-base insertion at 2319 (H773-V774ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 25 publications
(67 reference statements)
3
43
0
Order By: Relevance
“…However, modeling of EGFR A763insFQEA demonstrated that insertions before residue 764 do not exhibit this effect and do not induce drug resistance 16 . Moreover, in a patient-derived xenograft (PDX) model of NSCLC driven by an EGFR exon 20 mutation in which the insertions are in the loop after the α-C helix (EGFR H773insNPH), the third-generation EGFR TKIs osimertinib (AZD9291) and rociletinib (CO-1696) were found to have minimal activity 28 . In a recent study of rare EGFR and HER2 exon 20 mutations, the authors found a heterogeneous response to covalent quinazoline-based second-generation inhibitors, such as dacomitinib and afatinib; however, the concentrations that were required to target more common exon 20 insertion mutations were above what are clinically achievable 24 .…”
mentioning
confidence: 99%
“…However, modeling of EGFR A763insFQEA demonstrated that insertions before residue 764 do not exhibit this effect and do not induce drug resistance 16 . Moreover, in a patient-derived xenograft (PDX) model of NSCLC driven by an EGFR exon 20 mutation in which the insertions are in the loop after the α-C helix (EGFR H773insNPH), the third-generation EGFR TKIs osimertinib (AZD9291) and rociletinib (CO-1696) were found to have minimal activity 28 . In a recent study of rare EGFR and HER2 exon 20 mutations, the authors found a heterogeneous response to covalent quinazoline-based second-generation inhibitors, such as dacomitinib and afatinib; however, the concentrations that were required to target more common exon 20 insertion mutations were above what are clinically achievable 24 .…”
mentioning
confidence: 99%
“…If such similarity is systematically verified and further quantified, the translational utility of PDXs can be immensely explored and expanded. We have built a large library of PDXs over the years (7,8,(10)(11)(12)(13) and also performed transcriptome sequencing and/ or microarray analysis. The pathologic relevance of PDXs to patient tumors, both histologically and molecularly, can now be examined by comparing TCGA and PDX data.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, she has a rare mutation, which is an insertion mutation at exon 20 (p.V769_D770insASV). The majority of exon 20 insertion mutations reported to date are associated with resistance to TKIs (31,32). Her disease remained stable as of December 22, 2014, and the PFS is 36 months temporarily.…”
Section: Discussionmentioning
confidence: 99%